Early end-effector-based gait training in non-ambulatory patients with visuospatial neglect after subacute stroke - Gorsler, Anna; Ernst, Doreen; Grittner, Ulrike; Harnack, Daniel; Koßmehl, Peter; Mehrholz, Jan; Mueske, Carina; Schneider, Philipp; Kuelzow, Nadine (Frontiers in Neurology, 2025)
IntroductionEarly gait training plays a critical role in stroke rehabilitation, as reflected in relevant guidelines. However, patients with visuospatial neglect—a factor that negatively impacts gait recovery—have traditionally been excluded from robot-assisted gait training studies. To address this issue, our study examined the effects of end-effector-based gait training on subacute stroke patients with visuospatial neglect.MethodsA total of 43 patients were randomized in a controlled, assessor-blinded study and assigned either to end-effector-based gait training plus standard physical therapy or early verticalization with a standing frame plus standard physical therapy. All patients underwent nine training sessions over 2 weeks. We analyzed the primary outcome measure, the Functional Ambulation Category, using an ordinal regression model, reporting results for both the intention-to-treat population and the per-protocol sample, and also assessed trunk stability and balance as secondary outcomes.ResultsNeither the intention-to-treat analysis (odds ratio [95% confidence interval]: 1.20 [0.30–4.78]) nor the per-protocol analysis (odds ratio: 4.08 [0.80–20.87]) revealed any significant overall superiority of gait training compared to standing training. However, the per-protocol analysis showed a promising pattern: Severely affected patients were more likely to improve their walking ability after gait training depending on their baseline Functional Ambulation Category score. Gait training also led to greater improvements in trunk stability and balance than standing training did.ConclusionThese results suggest that early adjunctive end-effector-based gait training could benefit a subgroup of severely affected, non-ambulatory, subacute stroke patients with visuospatial neglect.Clinical trial registrationDRKS00021654, www.drks.de/search/de/trial/DRKS00021654.